An Individualized Recommendation for Controlled Ovary Stimulation Protocol in Women Who Received the GnRH Agonist Long-Acting Protocol or the GnRH Antagonist Protocol: A Retrospective Cohort Study - Chen, Ming-Xing; Meng, Xiang-Qian; Zhong, Zhao-Hui; Tang, Xiao-Jun; Li, Tian; Feng, Qian; Adu-Gyamfi, Enoch Appiah; Jia, Yan; Lv, Xing-Yu; Geng, Li-Hong; Zhu, Lin; He, Wei; et al. (Frontiers in Endocrinology, 2022)
Background The GnRH agonist long-acting protocol and GnRH antagonist protocol are widely used in ovarian stimulation. Which protocol eliciting higher live birth rate for IVF/ICSI patients with different ages, different ovarian reserves and different body mass index (BMI) has not been studied. However, among these protocols, the one that elicits higher live birth in IVF/ICSI patients with different ages, ovarian reserves and body mass indexes (BMI) has not been identified. Methods This was a retrospective cohort study about 8579 women who underwent the first IVF-ET from January, 2018 to August, 2021. Propensity Score Matching (PSM) was used to improve the comparability between two protocols. Results After PSM, significant higher live birth rates were found in the GnRH agonist long-acting protocol compared to GnRH antagonist protocol (44.04% vs. 38.32%) (p<0.001). Stratified analysis showed that for those with AMH levels between 3 ng/ml and 6 ng/ml, with BMI ≥ 24 kg/m2 and were aged ≥ 30 years old, and for those women with BMI < 24kg/m2 and were aged ≥30 years whose AMH levels were ≤ 3ng/ml, the GnRH agonist long-acting protocol was more likely to elicit live births [OR (95%CI), 2.13(1.19,3.80)], [OR (95%CI), 1.41(1.05,1.91)]. However, among women with BMI ≥ 24kg/m2 and were aged ≥30 years whose AMH levels were ≤ 3ng/ml, the GnRH agonist long-acting protocol had a lower possibility of eliciting live births [OR (95%CI), 0.54(0.32,0.90)]. Also, among women with AMH levels between 3 ng/ml and 6 ng/ml, with BMI ≥ 24 kg/m2 and with age < 30 years and for those with AMH levels between 3 ng/ml and 6 ng/ml, regardless of age, and with BMI<24kg/m2,, the possibility of live births was similar between the two protocols [OR (95%CI), 1.06(0.60,1.89)], [OR (95%CI), 1.38(0.97,1.97)], [OR (95%CI), 0.99(0.72,1.37)]. Among the women with AMH levels ≤ 3 ng/ml and with were aged < 30years, regardless of BMI, the possibility of live birth was similar between the two protocols [OR (95%CI), 1.02(0.68,1.54)], [OR (95%CI), 1.43(0.68,2.98)]. Moreover, among women with AMH levels ≥ 6ng/ml, the possibility of live birth was similar between the two protocols [OR (95%CI),1.42(0.75,2.69)], [OR (95%CI),1.02(0.19,5.35)], [OR (95%CI), 1.68(0.81,3.51)], [OR (95%CI), 0.51(0.10,2.55)]. Conclusions The suitability of the GnRH agonist long-acting protocol or GnRH antagonist protocol to infertility patients is dependent on specific biological characteristics of the patients.